2023
DOI: 10.1186/s12903-023-03378-0
|View full text |Cite
|
Sign up to set email alerts
|

The impact of periodontal disease on the clinical outcomes of COVID-19: A systematic review and meta-analysis

Sadeq Ali Al-Maweri,
Mohammed Nasser Alhajj,
Esam Halboub
et al.

Abstract: Background A possible relationship between periodontitis (PD) and COVID-19 and its adverse outcomes has been suggested. Hence, the present systematic review and meta-analysis aimed to investigate the available evidence regarding the potential association between periodontitis (PD) and COVID-19 and its adverse outcomes. Materials and methods PubMed, Scopus, Web of Science, and Google Scholar were searched for relevant studies published up to April 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…However, the shadows of uncertainty loom large concerning the long-term impacts, emphasizing the need for further, extensive research in this domain [47,48]. On the other hand, a systematic review and meta-analysis of 22 studies involving 92,535 patients from different regions found a significant association between periodontitis and adverse COVID-19 outcomes [49]. Patients with periodontitis are at higher risk for severe COVID-19 symptoms, ICU hospitalization, and death.…”
Section: Recent Clinical Insights Into the Intersection Of Periodonti...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the shadows of uncertainty loom large concerning the long-term impacts, emphasizing the need for further, extensive research in this domain [47,48]. On the other hand, a systematic review and meta-analysis of 22 studies involving 92,535 patients from different regions found a significant association between periodontitis and adverse COVID-19 outcomes [49]. Patients with periodontitis are at higher risk for severe COVID-19 symptoms, ICU hospitalization, and death.…”
Section: Recent Clinical Insights Into the Intersection Of Periodonti...mentioning
confidence: 99%
“…Severe periodontitis is particularly associated with worse outcomes than mild periodontitis. However, due to methodological differences between studies, further standardized studies are needed to fully understand the relationship between periodontal health and COVID-19 outcomes [49]. The human microbiota encompasses a diverse range of microbial communities residing within the host, including bacteria, viruses, fungi, and protozoans.…”
Section: Recent Clinical Insights Into the Intersection Of Periodonti...mentioning
confidence: 99%
“…Patients face the critical task of distinguishing between urgent and non-urgent dental care needs and must make informed decisions about seeking treatment [ 6 ]. While forgoing a dentist visit during a dental emergency can jeopardize oral health, unnecessary visits for non-emergency conditions may increase the risk of COVID-19 infection and negatively impact overall health [ 7 ].…”
Section: Introductionmentioning
confidence: 99%